When police kill - Zimring, Franklin E. (Harvard University Press, 2017)
When Police Kill is the first comprehensive analysis of police use of lethal force in the United States. The first seven chapters of this volume provide a summary and analysis of the known facts about killings by police. Who dies from police gunfire? What circumstances provoke police to shoot? Why is the death rate from shootings by police so high? Why are civilian deaths from police attacks so much higher in the United States than in other developed nations? Why are police also so much more at risk of death by assault than police in other nations? The final five chapters of the book provide an account of how federal, state and local governments can reduce killings by police without risking the lives of police officers. There are many strategies that federal and state government can use to motivate changes by police chiefs and sheriffs, but local law enforcement agencies are the main arena for reducing the carnage from police violence in the United States.--